Internationalization of Chinese currency - Ryabushkina, Anastasiya (My University, 2014)
China is the largest trading nation but the majority of it is carried out in US dollars. Currently the RMB is not even the top 3 most popular international currencies. The benefit and cost for China for making RMB an international currency must be weighed by the Chinese authorities. As the size of the economy and financial market increases and the monetary policy ftamework including exchange rate flexibility becomes more firmly established, the benefits should increasingly surpassed the costs.
Keywords: internationalization; China; Chinese currency; китайська валюта; Китай; інтернаціоналізація